2022
DOI: 10.52547/wjps.11.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in Cosmetic Services and Surgery among Iranian Households in 2019: A Decomposition Analysis

Abstract: Background The demand for cosmetic surgery is on the rise worldwide, making it the common form of surgery globally while the use of cosmetic surgery being exponentially high in Iran. The aim of this study was to investigate inequality in the use of cosmetic services and surgery (CSS) among Iranian households concerning demographic and socio-economic characteristics. Methods This study used data of 38960 Iranian household from the income-expenditure survey of the statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Although several people may feel more attractive and self-satisfied after conducting cosmetic interventions, some studies indicate that they might negatively impact their quality of life and mental health. 12 Some people may experience psychological disorders after cosmetic interventions, such as depression and suicidality, and some may develop an addiction to cosmetic interventions. 13 Additionally, like all medical interventions, cosmetic surgery may lead to multiple potential undesirable consequences, including cardiac disorders, nerve damage, and infections.…”
mentioning
confidence: 99%
“…Although several people may feel more attractive and self-satisfied after conducting cosmetic interventions, some studies indicate that they might negatively impact their quality of life and mental health. 12 Some people may experience psychological disorders after cosmetic interventions, such as depression and suicidality, and some may develop an addiction to cosmetic interventions. 13 Additionally, like all medical interventions, cosmetic surgery may lead to multiple potential undesirable consequences, including cardiac disorders, nerve damage, and infections.…”
mentioning
confidence: 99%
“…As the top-income quintile becomes wealthier, their expenditure on cosmetic procedures increases, indicating an intensified desire to improve physical appearance using their available resources. 18 Concurrently, these tendencies might mirror the societal pressures this group faces to maintain a certain level of physical attractiveness. Faced with both internal desires and external expectations, the affluent set societal standards of attractiveness, increasingly difficult for the lowerincome population to achieve.…”
Section: Discussionmentioning
confidence: 99%
“…As the top-income quintile becomes wealthier, their expenditure on cosmetic procedures increases, indicating an intensified desire to improve physical appearance using their available resources 18 . Concurrently, these tendencies might mirror the societal pressures this group faces to maintain a certain level of physical attractiveness.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that individuals with higher socioeconomic status and educational levels show a trend towards cosmetic enhancements, possibly due to greater access to information and resources. However, Ramandi et al showed that several other factors are associated with growing interest in cosmetic procedures including older age, having children, higher household income, lower education, and greater acceptance of media images [ 21 ].…”
Section: Discussionmentioning
confidence: 99%